Budaya Organisasi Dan Kepemimpinan Transformasional: Sistematika Tinjauan Literatur - Jamilatul Hasanah; M. Zainal Alim; Vicky Febriansyah; Mochammad Isa Anshori (Jurnal Ilmiah Dan Karya Mahasiswa, 2023)
According to Saputra and Rumangkit (2021), one of the factors that can affect organizational commitment is organizational culture, because organizational culture is an identity that exists in an organization that distinguishes organizational culture from other companies. High commitment from employees is what the company really wants. The more highly committed employees, the overall company productivity will increase, and the company can survive in its business competition. Commitment to the organization is an important behavioral dimension that can be used to evaluate the strength of workers to stay in an organization. Therefore, the management of an organization or company needs to continue to encourage the creation of commitment from members of the organization. Several factors that can increase organizational commitment are carried out through the role of transformational leadership and organizational culture.